The therapeutic effects of Juglans regia Linn (Walnut) extracts on oral Candida infection - Hamida, Talia; Bouderba, Nora Nahal; Slimani, Alaa (Journal of Agriculture and Applied Biology, 2024)
The difficulties associated with oral Candida infection management necessitate the development of novel antifungal medicines in order to widen the spectrum of activity against Candida albicans. The aim of this work is to study the oral anticandidal activity of Juglans regia L. cultivated in Algeria. This plant was chosen due to its traditional use for the treatment of oral infections. Methanolic, ethanolic, butanolic, ethylic acetate and acetonic extracts of the bark of J. regia L. were extracted in a Soxhlet device and screened for in vitro activity against C. albicans. Plant preparations were screened for antifungal activity using a standard agar well diffusion assay. Following a study of the antimicrobial activity of plant extracts, their minimal inhibitory concentration (MIC) and minimal fungicidal concentration (MFC) values were determined using a broth microdilution assay. Among J. regia L. extracts, ethylic acetate extract had potent antifungal activity against Candida strain with diameters of inhibition ranging from 15.16±0.76 to 20.83±0.76 mm, followed by acetonic extract with diameters of inhibition ranging from 14.83±0.76 to 19.33±0.28 mm. The J. regia L. demonstrated MIC values ranging from 0.46875 to 3.75 mg mL-1 and the lowest MIC was recorded for ethylic acetate, acetonic extracts and AMB at 0.46875 mg mL-1. The ethylic acetate extract showed the lowest MFC value (0.9375 mg mL-1), followed by butanolic extract (3.125 mg mL-1). These results indicate that J. regia L. bark extracts can contain compounds with therapeutic potential against oral C. albicans and, hence, their possible use as therapeutic agents for oral candidiasis.